P20 The Sikh population of North West Kent: exploring the lived experience of caring for a dying relative at home. (1st October 2013) - Cowan, Margaret Mary; Withell, Bridget
Abstract : Research Aims: To explore the Sikh population's experience of caring for a dying relative at home and develop an understanding of their experiences. Background /literature review: Hill & Penso, (1995) reported under-use of specialist palliative care services by minority ethnic groups with minimal improvement noted in present day (Gunaratnam, 2007, DoH, 2008). Often, end-of-life needs are unfulfilled ( Worth et al, 2009, DoH, 2010, DoH, 2011). Locally, Sikhs account for 12.8% of the population although only 1% of referrals to local hospice are Sikh. Method: A qualitative study, facilitating interviews in Punjabi and English, using interpretative phenomenological analysis to analyse the transcribed data. Results/Discussion: Five super-ordinate themes identified: Factors leading to the caring role; Emotional effects of caring on the carer Impact of caring on the wider family Influence of the health care services Religious and cultural influence Lack of support from health care professionals emerged as an overriding theme An overwhelming sense of duty pervaded each family sustaining them to cope. The option of their relative being nursed in care home/hospice was unlikely as participants reported fears that care could only be received if it was paid for. Culture and religion played an important role in the caring role. Conclusions: GPs and hospices need to take a major role in identifying patients with non-malignant disease to ensure referral to other services. Access to equipment is uncoordinated. Financial concerns over care are apparent in this population. Sikh carers need to be educated and supported to continue to support their relatives. Applications to hospice practice: Allows equity of care to patients dying of non-malignant disease. Improves bereavement support for this population. Engagement with community may need to extend to outreach clinics to raise awarenss within this population. Extends education on end-of-life issues to this minority ethnic group.